Diel variation in the catch of the shrimp Farfantepenaeus duorarum (Decapoda, Penaeidae) and length-weight relationship, in a nursery area of the Terminos Lagoon, Mexico - Brito, Roberto; Gelabert, Rolando; Amador del Ángel, Luís Enrique; Alderete, Ángel; Guevara, Emma (Revista de Biología Tropical, 2017)
The pink shrimp, Farfantepenaeus duorarum is an important commercial species in the Gulf of Mexico, which supports significant commercial fisheries near Dry Tortugas, in Southern Florida and in Campeche Sound, Southern Gulf of Mexico. There is information about the nictemeral behavior of the pink shrimp related to sunset, what is crucial to more accurate estimation of shrimp population biomass, and to assess the potential of this resource and its proper management. To contribute to the knowledge and the population dynamics of the species, shrimp surveys were conducted in a nursery area near “El Cayo” in the Northeastern part of Terminos Lagoon, Mexico during October 2010. Three sampling sites with substrate covered by submerged vegetation were chosen; two set of samples were collected at each site, one in the morning and the other just after sunset. Three trawls were performed per sampling site using a small otter trawl. A total of 1 418 shrimp (between 5.5 to 28.8 mm Carapace Length (CL)) were collected during the study; 1 416 F. duorarum and only two individuals of Litopenaeus setiferus. Shrimps CL and Total Length (TL) were measured in mm and individuals were weighted to the nearest 0.01 g. In general, shrimp biomass and density were significantly higher in all sites during dusk (biomass = 46.36 g.100 m-2, n = 1 344), than daylight samples (biomass = 2.78 g.100 m-2, n = 72). The One-way ANOVA and the Tukey test performed to evaluate variability in CL found significant differences between sites (CL = 14.12 mm, 12.46 mm and 15.13 mm, for site 1, 2 and 3 respectively, F = 64.92, P < 0.001) which might be related to the substrate type. The length-weight relationships reflected positive allometric growth for juveniles but isometric for subadults and two nonlinear power functions were estimated (W = 0.0004CL3.157 for juveniles, and W = 0.0009CL2.902 for subadults). The results of the analysis of covariance (ANCOVA) test indicated that the Total Length - Carapace Length (TL-CL) relationships were significantly different between juveniles and subadults, and two linear equations (TL = 2.615 + 4.476CL and TL = 8.931 + 4.062CL for juveniles and subadults respectively) were fitted. It is important that population assessment takes into account the day or night period as a bias factor when sampling the abundance of the juveniles of F. duorarum in this important nursery ground of the Campeche Sound.